Law, social science, and the criminal courts - Smith, Alisa (Carolina Academic Press, 2020)
Brief introduction to the courts and evidence -- The history of social science in the law -- The legal aspects of social science -- Social science as evidence in court -- Expectation of privacy and the Fourth Amendment -- Police stops and seizures -- The exclusionary rule -- Pretrial publicity, cameras in the courtroom, and social media effects on the fair trial - right to counsel -- Six persons, a fair cross-section, and unanimous verdicts : The right to a jury trial -- Eyewitness and mistaken identifications -- Miranda and false confessions -- Future dangerousness and the offender -- Life or death : the ultimate punishments.